Monisothermal Poiseuille Flow of a Newtonian Fluid with Temperature Dependent Viscosity - Nowak, Z.; Rup, K. (Engineering Transactions, 1981)
In the present paper an attempt is made to apply the method of Vujanovic to the nonisothermal flow of a Newtonian fluid in a circular pipe. It is assumed that the dynamic viscosity of the fluid varies with temperature in a prescribed manner. By using the concept of "penetration depth" the problem under consideration is solved in two stages. Both the temperature and velocity distributions are determined approximately. The results obtained are compared with the numerical solution given recently in [4].